LEARNING GEOMETRY AND ALGEBRA: ETHNOMATHEMATICS ON THE GRAND MOSQUE OF ALJABBAR (Proceedings of the International Conference on Future of Education, 2024)
This study aims to explore the concepts of geometry and algebra used in mosque buildings using a qualitative approach to ethnographic methods. This study uses the Grand Mosque of Al-Jabbar as a sample located in Bandung, West Java, Indonesia, because the mosque since its inauguration has invited public enthusiasm by presenting a new history of beautiful and magnificent mosque architecture. Triangulation techniques were used to generate valid data through observation, documentation (photos and videos), interview, and literature studies in the form of studies on building structures. The results of this study show that the building structures of the Grand Mosque of Al-Jabbar contain elements of plane geometry, namely triangle, square, rectangle, hexagon, and circle. There are also elements of three-dimensional geometry, namely, pyramid, prism, and tube. The concept of number patterns can be found in the arrangement of mosque domes which have patterns 1, 2, 4, 5, 10. Based on this, the construction of the Grand Mosque of Al-Jabbar contains geometry and algebra concepts that can be used as an alternative to contextual learning, so that students can know the meaning of mathematics learned at school and have the ability to solve problems in real life. Ethnomathematics learning can also be applied through online learning.
Keywords: Ethnomathematics; Mosque; Al-Jabbar; Geometry; Algebra; Online Learning